2017
DOI: 10.1016/j.phymed.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A standardized Humulus lupulus (L.) ethanol extract partially prevents ovariectomy-induced bone loss in the rat without induction of adverse effects in the uterus

Abstract: Background Hops (Humulus lupulus (L.)) dietary supplements are of interest as herbal remedies to alleviate menopausal symptoms, such as hot flushes, depression and anxiety. So far, the evidence regarding estrogenic and related properties of hops preparations has been considered insufficient for a market authorization for menopausal indications. Purpose The study aims to investigate a chemically standardized hops extract regarding its safety in the uterus, as wells as its efficacy to prevent bone loss in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“… 7 Ex3 has been proven to be safe in different animal studies and showed moderate activity in an osteoporosis animal model. 57 In the case where certain bioactivities might be unintended, it is desirable to “knock-out/-down” the underlying bioactive compounds, thereby reducing unwanted or even adverse effects. For example, premenopausal women may seek natural chemopreventive agents, such as hop extracts, without estrogenic potential.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 7 Ex3 has been proven to be safe in different animal studies and showed moderate activity in an osteoporosis animal model. 57 In the case where certain bioactivities might be unintended, it is desirable to “knock-out/-down” the underlying bioactive compounds, thereby reducing unwanted or even adverse effects. For example, premenopausal women may seek natural chemopreventive agents, such as hop extracts, without estrogenic potential.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The basal setup for the experimental procedures for this part of the experiment are described in connection with the report on the results on bone and uterus from the same study [27] and are schematically depicted in Fig. 1A.…”
Section: Methodsmentioning
confidence: 99%
“…Some have shown that 8-PN ( 4 ) has osteoprotective effects on the tibia [ 64 , 82 , 83 , 84 ] while Hoffmann et al did not confirm the protective effect of 8-PN ( 4 ) at a safe dose due to cancer in primary bone osteoporosis [ 85 ]. Keiler et al provided evidence of the safety of using standardized hops extract (no proliferation in the endometrium) and showed a weak protective effect of the extract on bone loss after estradiol ( 20 ) depletion in ovariectomized rats [ 86 ].…”
Section: Phytoestrogensmentioning
confidence: 99%